2005
DOI: 10.1248/bpb.28.919
|View full text |Cite
|
Sign up to set email alerts
|

The Favorable Effect of Style of Zea mays L. on Streptozotocin Induced Diabetic Nephropathy

Abstract: The effectivity of water extract from the style of Zea mays on diabetic nephropathy was investigated in the development of new natural medicinal resources. Streptozotocin (STZ) induced diabetic rats were used to evaluate the therapeutic effect of the style. Urinary albumin excretion and creatinine clearance were examined for diagnosis of diabetic nephropathy. From these results it was learned that the style of Z. mays prevented glomerular hyperfiltration. The present findings indicated that the water extract o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 6 publications
1
10
0
1
Order By: Relevance
“…Elevated blood glucose can damage the cells and microblood vessels of the kidney [28]. Our previous study found that FPS affected chronic renal failure and diabetic complications [15,22].…”
Section: Resultsmentioning
confidence: 99%
“…Elevated blood glucose can damage the cells and microblood vessels of the kidney [28]. Our previous study found that FPS affected chronic renal failure and diabetic complications [15,22].…”
Section: Resultsmentioning
confidence: 99%
“…In Mexico this preparation is also used to manage diabetes (Andrade-Cetto et al, 2006;Andrade-Cetto and Heinrich, 2005). Accordingly, Suzuki et al (2005) showed a positive effect of the style of this species on streptozotocin-induced diabetic nephropathy (Suzuki et al, 2005). The flavones, chrysoeriol 6-C-β-boivinopyranosyl-7-O-β glucopyranoside and chrysoeriol 6-Cβ-L-boivinopyranoside, have been isolated from the style of this species, and they exhibited glycation inhibitory activity (Suzuki et al, 2003), which provides some scientific explanation for the traditional use for diabetes in Mexico.…”
Section: Plant Species Used To Treat Diabetes and Its Sequelae In Cenmentioning
confidence: 99%
“…Corn silk (CS), which is the yellowish thread-like strands from corn herbal hwabongwa (Zey mays L.), has been used as treatments for obesity, kidney-related diseases, neurodegenerative diseases, and diabetes [ 3 4 5 6 7 8 9 10 11 12 13 ]. CS extract includes various bio-functional substances such as tartaric acid, isoquercitrin, allantoin, stigmasterol, hordenine, maysin, resin, cryptoxanthin, and anticyanins [ 14 15 ].…”
Section: Introductionmentioning
confidence: 99%